Kidnapped - Stevenson, Robert Louis; Hite, Sid (New York Franklin Watts, 2007)
A sixteen-year-old orphan is kidnapped by his villainous uncle, but later escapes and becomes involved in the struggle of the scottish highlanders against english rule
American Corner
Includes a study guide and glossary
Originally Published in 1887
8 11
Keywords: Adventurers -- Fiction; English Fiction; English Stories